Lophatherum gracile Brongn. attenuates neutrophilic inflammation through inhibition of JNK and calcium. (10th January 2021) - Lai, Kuei-Hung; Chen, Po-Jen; Chen, Chih-Chuan; Yang, Sien-Hung; El-Shazly, Mohamed; Chang, Yu-Chia; Wu, Yi-Hsuan; Wu, Yi-Hsiu; Wang, Yi-Hsuan; Hsieh, Hsi-Lung; Hwang, Tsong-Long
Abstract: Ethnopharmacological relevance: Lophatherum gracile Brongn. ( L. gracile ) has been long used in traditional herbal medicine to clinically clear heat, disinhibit dampness, and treat inflammation. However, the effect of L. gracile on the activation of human neutrophils remains unclear. Aim of the study: The aim of current study is to investigate the anti-inflammatory properties of L. gracile extract (LGE) in N -formyl-methionyl-leucyl-phenylalanine (fMLF)-induced activation of human neutrophils. Materials and methods: Superoxide anion generation and elastase release were estimated by spectrophotometry. A series of signaling pathways including mitogen-activated protein kinases (MAPKs) and protein kinase B (Akt), as well as calcium mobilization were studied by Western blot analysis and spectrofluorometry. Results: Our experimental results indicated that the nontoxic dosage of LGE does-dependently inhibited the fMLF-induced superoxide anion (O2 − ) generation, elastase release, CD11b expression, adhesion, and chemotactic migration in human neutrophils. LGE selectively inhibited the fMLF-induced phosphorylation of JNK but not p38, ERK, or Akt in human neutrophils. LGE also decreased the intracellular Ca 2+ levels ([Ca 2+ ]i ) in fMLF-activated human neutrophils. However, a specific JNK inhibitor inhibited the fMLF-induced O2 − generation and CD11b expression, but it had no effect on [Ca 2+ ]i in human neutrophils. Conclusions: LGE exhibited anti-inflammatory activities in fMLF-activated human neutrophils. The pharmacological mechanisms of LGE-repressed neutrophilic inflammation were through two independent pathways, JNK signaling and calcium mobilization. Our results suggested that LGE holds the potential to be developed as an anti-inflammatory botanical medicine. Graphical abstract: Image 1